Analysis of Peat Soil Characteristics (Histosol) at Several Maturity Levels in Oil Palm (Elaeis guineensis Jacq.) Plantations in Lubuk Sakat Village, Kampar - Patra Anjara Ginting; Wawan; Fifi Puspita; Cynthia Bernadetta Silalahi; Asri Cahyati Zebua (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Agricultural development on peatlands requires a careful and thoughtful approach. Therefore, conducting an inventory of their characteristics is essential for ensuring proper utilization and effective planning. This study aims to analyze the characteristics of peat soils in Lubuk Sakat Village, Kampar, Riau, which are planted with oil palm at various maturity stages, covering a potential peatland area of approximately 800 hectares. The research was conducted using observational and descriptive methods, with purposive sampling employed at peatlands of fibric, hemic, and sapric maturity stages. The observed soil characteristics included pH, organic carbon (C-Organic), available phosphorus (P-Available), and cation exchange capacity (CEC). In addition to these chemical properties, the soil microbial population was also assessed. The results revealed that soil pH, C-Organic, and CEC were similar across the three maturity stages, while P-Available was higher in sapric and hemic peat compared to fibric peat. The microbial population was found to be highest in sapric peat, followed by hemic peat, and lowest in fibric peat. These findings are expected to provide a solid foundation for managing fertilization and improving oil palm productivity on peatlands with similar characteristics.